Pharmacokinetic and Pharmacodynamic Comparison of Sildenafil‐Bosentan and Sildenafil‐Ambrisentan Combination Therapies for Pulmonary Hypertension. Issue 1 (12th January 2016) - Hakamata, A; Odagiri, K; Miyakawa, S; Irisawa, H; Takeuchi, K; Inui, N; Tanaka, S; Uchida, S; Watanabe, H
Abstract : To elucidate whether the pharmacokinetics (PK) and pharmacodynamics (PD) of sildenafil are influenced differently when it is coadministered with bosentan (S+B) or with ambrisentan (S+A), we evaluated the PK and PD profiles of sildenafil before and after 4–5 weeks of S+A or S+B treatment in patients with pulmonary arterial hypertension. The area under the plasma concentration–time curve of sildenafil was significantly higher in S+A treatment than in S+B treatment (165.8 ngh/mL vs. 396.8 ngh/mL, P = 0.018) and the oral clearance of sildenafil was significantly lower after S+A treatment than after S+B treatment (120.6 L/h/kg vs. 50.4 L/h/kg, P = 0.018). In the PD study, incremental shuttle walking distance was superior during treatment with S+A than during treatment with S+B (S+B; 280 m vs. S+A; 340 m, P = 0.042). There were no concerns about safety with either combination therapy regime.